2020
DOI: 10.3126/jaar.v7i1.35467
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception Regarding Hypertension among Hypertensive Patients at a Tertiary Hospital in Kathmandu, Nepal

Abstract: Background: Hypertension has a great impact on cardiovascular disease and death all over the world. Low and middle-income countries including Nepal are facing higher disease burden because of complications arise from uncontrolled hypertension. Patient’s knowledge and perception play an important role for the proper management of hypertension. There are limited studies related to knowledge and perception of hypertension, therefore, this study aimed to assess the knowledge and perception of hypertension among hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…This was consistent with a study in Nepal that reported a significant association between HTN duration of 10–15 years and overestimation of CVD risk. 80 In the present study, the duration of HTN exhibited a U-shaped pattern with 10–14 years as the peak, which suggests the importance of disease over time on CVD risk perceptions. In the original Framingham Heart Study, the progression of HTN to target organ diseases (TOD) such as HF and other CVD complications had a mean of 14 years.…”
Section: Discussionsupporting
confidence: 52%
“…This was consistent with a study in Nepal that reported a significant association between HTN duration of 10–15 years and overestimation of CVD risk. 80 In the present study, the duration of HTN exhibited a U-shaped pattern with 10–14 years as the peak, which suggests the importance of disease over time on CVD risk perceptions. In the original Framingham Heart Study, the progression of HTN to target organ diseases (TOD) such as HF and other CVD complications had a mean of 14 years.…”
Section: Discussionsupporting
confidence: 52%